Reconstruction of hydrographic changes in the southern Norwegian Sea during the past 135 kyr and the impact of different foraminiferal Mg/Ca cleaning protocols - Ezat, Mohamed; Rasmussen, Tine Lander; Groeneveld, Jeroen (Geochemistry, Geophysics, Geosystems, 2016)
The shallow subsurface hydrography in the southern Norwegian Sea during the past 135,000 years was investigated using parallel measurements of Mg/Ca and δ18O in shells of the planktic foraminiferal species Neogloboquadrina pachyderma. Two cleaning methods were applied prior to Mg/Ca analysis, “Mg cleaning” and “full cleaning” methods. Different results were obtained, which are most likely due to a more efficient removal of Mn-contaminant coatings of the shells, when the “full cleaning” procedure was applied. We further combined Mg/Ca and B/Ca from the “full cleaning” method with δ18O values to constrain the calcification temperature and seawater-δ18O (δ18Osw) in the past. During Heinrich Stadial (HS)1 (∼18.5–15 ka) N. pachyderma constituted >80% of the planktic foraminiferal population, δ18Osw decreased by ∼1.5‰, and shallow subsurface temperature increased by ∼1.5–3°C, suggesting strong stratification in the upper water column and a possible subsurface inflow of Atlantic water below a well-developed halocline during the calcification seasons of N. pachyderma. Similar decreases in δ18Osw are also recorded for other Heinrich stadials (HS2, 3, 4, 6, and 11). Our temperature estimates confirm previous observations of the delay of the last interglacial “Eemian” warm peak in the eastern Nordic Seas compared to the North Atlantic, and a late warming coinciding with the summer insolation minimum at 60°N. In addition, relatively high values of δ18Osw during the early Eemian suggest a shallow subsurface inflow of Atlantic water below a thin layer of Arctic surface water.